Analysis of A Pieces Framework of A Localhost Web-Based Income Statement EPOSAL Application - Dyah, Dyah Mustikasari; Karaman, Jamilah; Cobantoro, Adi Fajaryanto (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2022)
Measuring the quality of a system must be conducted. This is useful for repairing the damage that may be in the system that has been created. One thing that can be measured in a system is to measure the level of satisfaction of a system. Many methods can be used to measure the level of satisfaction, one of which is the PIECES framework method. PIECES framework is a series of activities that measure the level of happiness based on six variables: performance, information, economics, control and security, efficiency, and service. One of the systems that can be analyzed is the system contained in the EPOSAL application. EPOSAL is a localhost web-based application that can be used to create an income statement. The sample in this study was respondents who used this EPOSAL application. The instrument used was a questionnaire. Data analysis was carried out by following the PIECES calculation provisions. After analyzing the data, it is known that for the variables Performance, Economics, Control, and Security and Service, the satisfaction level is at the "Very Satisfied" level. As for the Efficiency, Information, and Efficiency variables, the level of satisfaction is at the "Satisfied" level.